DERAJAT DESENTRALISASI FISKAL DAN KEMANDIRIAN DAERAH KOTAMADYA METRO DAN LAMPUNG TIMUR - Rahmawati, Rita (Fakultas Ekonomi dan Bisnis Universitas Ahmad Dahlan, 2011)
Part of Regional Otonomy in financeÂ is giving local governmentÂ to arrange regional receipt to purchase expenses bugget. Government genuine Receipt is one regional receipt that shows how stronger local goverment finance can handled all the expenditure, not only depend on Central Government. Metro and Lampung Timur same with another local government in Indonesia, wants the higher regional otonomy espescialy in finance. The higher decentralization indicate higher ability on local government to fulfill all expenditure. In can be analized from share of Government Genuine Receipt and Tax and non Tax Share compare Total Regional Receipt and Total Regional Expenditure. Higher fiscal Desentralization needed by Metro and Lampung Timur to get higher Regional otonomy.